Effect of the addition of wild legumes (Lathyrus annuus and Lathyrus clymenum) on physical and nutritional properties of extruded products based on whole corn and brown rice - Pastor Cavada, Elena (2011)
The effects of the addition of wild legumes (Lathyrus) from the South of Spain on the physical and nutritional properties of extruded products based on whole corn and brown rice were studied. Samples were obtained with a Brabender single screw extruder. The physical characterization of the expanded products was performed by the measurement of density, expansion, solubility and specific mechanical energy consumption (SMEC). Chemical composition, amino acids content, protein digestibility, total polyphenol content and potential availability of iron and zinc were determined. Results showed that expansion, solubility and SMEC were higher for rice blends than for corn blends, while density followed an inverse trend. Addition of legumes produces a decrease of expansion and an increase in solubility in both rice-containing and corn-containing samples. With only 15% of legume replacement, a significant increase in protein content and quality, fiber, and mineral content was obtained. Protein digestibility was in the range of 82-84% and mineral availability in the 6.4-12.1% range for iron and 10-18.6% for zinc. The performance of each mixture during extrusion and the physical properties of the extruded products were considered to be in the range of those expected for snack type products.